Capital Structure Decisions : Evaluating Risk and Uncertainty - Agarwal, Yamini (Wiley corporate F & A series., 2013)
"Practical ways of determining capital structures have always been mysterious and riddled with risks and uncertainties. Dynamic paradigm shifts and the multi-dimensional operations of firms further complicate the situation. Financial leaders are under constant pressure to outdo their competitors, but how to do so is not always clear. Capital Structure Decisions offers an introduction to corporate finance, and provides valuable insights into the decision-making processes that face the CEOs and CFOs of organizations in dynamic multi-objective environments. Exploring the various models and techniques used to understand the capital structure of an organization, as well as the products and means available for financing these structures, the book covers how to develop a goal programming model to enable organization leaders to make better capital structure decisions. Incorporating international case studies to explain various financial models and to illustrate ways that capital structure choices determine their success, Capital Structure Decisions looks at existing models and the development of a new goal-programming model for capital structures that is capable of handling multiple objectives, with an emphasis throughout on mitigating risk"--EBL